2018
DOI: 10.58843/ornneo.v29i1.359
|View full text |Cite
|
Sign up to set email alerts
|

Social Organization and Food Habits of the Acorn Woodpecker (Melanerpes Formicivorus) in the Neotropics Including Observations in Central Honduras

Abstract: ∙ Acorn Woodpeckers (Melanerpes formicivorus) have been widely studied in North America, mainly due to their complex social system. As a resident bird, Acorn Woodpeckers in much of North America hoard acorns for use during the winter and following spring. The importance of this resource, along with geographic differences in the woodpecker’s ecology, has not been as widely studied elsewhere in its range, which extends all the way through Middle America to northern Colombia. This review summarizes published rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…It has been suggested that the first rains stimulate the initiation of the reproductive cycle, which begins with the excavation of nests and laying of eggs. Thereafter, as incubation and hatching progresses, the rains increase as does the availability of food for both the offspring and the adults Sherry 2006, Flores andArdón 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the first rains stimulate the initiation of the reproductive cycle, which begins with the excavation of nests and laying of eggs. Thereafter, as incubation and hatching progresses, the rains increase as does the availability of food for both the offspring and the adults Sherry 2006, Flores andArdón 2018).…”
Section: Discussionmentioning
confidence: 99%